TINGKAT KEPUASAN KERJA PETUGAS SATUAN POLISI PAMONG PRAJA (SATPOL PP) KOTA CILEGON - Mujib Mujib; Ihin Solihin Ihin Solihin (NIAGARA Scientific Journal, 2018)
The existence of changes, improvements and improvement of work discipline Satpol PP Officers by way of fulfillment of compensation and adequate job satisfaction. It is hoped that Satpol PP Satpol PP will increase and able to substitute the quantity of existing officers so that the implementation of guidance, supervision, service to the community and other official implementation can be implemented maximally. The method used by this research is descriptive qualitative method, where the researcher is a key instrument, sampling of data source is done purposively, collecting technique with triangulation, data analysis is inductive / qualitative, and qualitative research results emphasize the meaning of generalization. Qualitative research relies on a holistic naturalbackground, positioning humans as a research tool, conducting inductive data analysis, prioritizing the process rather than results and the results of research undertaken agreed by the researcher and the research subject. The results of the discussion in the previous chapter it can be concluded that Satpol PP Satpol PP Job Satisfaction is considered good enough that seen from 2 factors namely Factors Theory and Value Theory. As the results of research conducted show that Factor Theory and Value Theory clearly seen that various aspects considered quite good and need to be improved again.